Coblation-assisted management of pediatric airway stenosis. (August 2016) - Fastenberg, Judd H.; Roy, Soham; Smith, Lee P.
Abstract: Objectives: The treatment of pediatric airway stenosis represents a major challenge for the otolaryngologist. The aim of this study is to evaluate the use of bipolar radiofrequency plasma ablation (Coblation) in the treatment of pediatric airway stenosis. Study design: Retrospective case series. Tertiary care pediatric academic medical center. Methods: The medical records of 6 pediatric patients at Cohen Children's Medical Center from July 2009 to December 2015 were reviewed. All cases involved the use of radiofrequency plasma ablation to address airway stenosis. Patient presentation, surgical intervention(s), post-operative course and complications were analyzed. Results: All 6 cases involved pediatric airway stenosis, including glottic stenosis (2), bilateral vocal fold immobility (2), and intratracheal lesions (2). Coblation was used to perform a range of different procedures, including removal of scar/granulation tissue, partial arytenoidectomy, and posterior cordectomy. All patients experienced good results without major complications, perioperative, or post-operative sequellae. Conclusion: The results of this study suggest that radiofrequency plasma ablation may be an effective endoscopic tool for the treatment of pediatric airway stenosis. Further study and more patients are required as this technique becomes increasingly applied.